Post onset, oral rapamycin treatment delays development of mitochondrial encephalopathy only at supramaximal doses. (1st May 2017) - Felici, Roberta; Buonvicino, Daniela; Muzzi, Mirko; Cavone, Leonardo; Guasti, Daniele; Lapucci, Andrea; Pratesi, Sara; De Cesaris, Francesco; Luceri, Francesca; Chiarugi, Alberto
Abstract: Mitochondrial encephalopathies are fatal, infantile neurodegenerative disorders caused by a deficit of mitochondrial functioning, for which there is urgent need to identify efficacious pharmacological treatments. Recent evidence shows that rapamycin administered both intraperitoneally or in the diet delays disease onset and enhances survival in the Ndufs4 null mouse model of mitochondrial encephalopathy. To delineate the clinical translatability of rapamycin in treatment of mitochondrial encephalopathy, we evaluated the drug's effects on disease evolution and mitochondrial parameters adopting treatment paradigms with fixed daily, oral doses starting at symptom onset in Ndufs4 knockout mice. Molecular mechanisms responsible for the pharmacodynamic effects of rapamycin were also evaluated. We found that rapamycin did not affect disease development at clinically-relevant doses (0.5 mg kg −1 ). Conversely, an oral dose previously adopted for intraperitoneal administration (8 mg kg −1 ) delayed development of neurological symptoms and increased median survival by 25%. Neurological improvement and lifespan were not further increased when the dose raised to 20 mg kg −1 . Notably, rapamycin at 8 mg kg −1 did not affect the reduced expression of respiratory complex subunits, as well as mitochondrial number and mtDNA content. This treatment regimen however significantly ameliorated architecture of mitochondria cristae in motor cortex and cerebellum. However, reduction of mTOR activity by rapamycin was not consistently found within the brain of knockout mice. Overall, data show the ability of rapamycin to improve ultrastructure of dysfunctional mitochondria and corroborate its therapeutic potential in mitochondrial disorders. The non-clinical standard doses required, however, raise concerns about its rapid and safe clinical transferability. Highlights: Daily treatment with oral rapamycin improves Ndufs4 KO mice phenotype and survival. Clinically relevant doses of rapamycin are not effective in Ndufs4 KO mice. Rapamycin does not counteract reduced respiratory complex subunit expression. Rapamycin treatment induces remodeling of mitochondria cristae in the CNS.